Efeito da temperatura de incubação e de criação sobre o tecido adiposo e desempenho de frangos de corte - Almeida, Vitor Rosa de [UNESP] (2013)
This work is structured in 4 chapters. Chapter 1 consists of a literature review on the topic. In Chapter 2 we analyzed whether manipulating incubation temperature at the fetal stage interferes with fat deposition in newly hatched chicks. The yolk-sack composition, size and proliferation of adipocytes in different regions of the body and incubation parameters and blood were analyzed. The hatching rate and incidence of non-incorporation of yolk and open umbilical region were higher at 39ºC. Adipocytes were higher in the abdominal region than in the cervical and legs, while the neck had more mitoses and increased number of adipocytes, and 39ºC decreased adipocyte size. Incubation at 36ºC caused less water use, dry matter, fat, ash, crude protein and yolk-sac use without change in body weight of chicks at hatching, showing better mass conversion under incubation at 36ºC as compared to 37.5 and 39. In Chapter 3 the performance, carcass and cut yield and blood parameters of broilers hatched from eggs incubated at 36ºC, 37.5ºC or 39ºC and raised at temperature recommended for the strain (L), the preference temperature (P) or warm (Q), using an experimental design consisting of eight treatments: 36ºC-L, 36ºC-P, 36ºC-Q, 37.5ºC-L, 37.5ºC-P, 37.5ºC-Q, 39ºC-PL, 39ºC-Q. The strain (L) and preference tempature (P) of chickens for eggs incubated at 39°C coincided. We concluded that a warm environmental temperature affects the performance of broilers regardless of incubation temperature, but broilers incubated at 39ºC can better maintain blood homeostasis under this setting...